The Relationship Between Anxiety Levels and Premenstrual Syndrome (PMS) Among Female Adolescents at Mulia Karya Husada Health Vocational School: Hubungan Tingkat Kecemasan Dengan Premenstrual Syndrome (Pms) Pada Remaja Puteri Di Smk Kesehatan Mulia Karya Husada - Febrianti, Dwinara; Lia Fitriyanti; Nuhan, Helena Golang (Universitas Mohammad Husni Thamrin, 2025)
Adolescence is an important phase in the physical, psychological, and social development of individuals. Female adolescents experience significant hormonal changes, particularly related to the menstrual cycle, which often causes both physical and psychological discomfort. One of the common problems faced is Premenstrual Syndrome (PMS), which is characterized by various physical and psychological symptoms such as mood swings, anxiety, depression, fatigue, breast tenderness, bloating, and changes in sleep patterns that affect different aspects of life. Anxiety experienced by adolescents during PMS is often overlooked, yet it can significantly affect their quality of life if there is no effective intervention to reduce its negative impacts. The aim of this study is to determine the relationship between anxiety levels and Premenstrual Syndrome (PMS) among female adolescents at Mulia Karya Husada Health Vocational School. This study employed a cross-sectional design. The research sample consisted of 153 female adolescents at Mulia Karya Husada Health Vocational School. Data were collected using questionnaires. The results showed that the majority of respondents experienced mild anxiety (141 students, 92%) and the majority did not experience Premenstrual Syndrome (130 students, 85%). The analysis using the chi-square test revealed a significant relationship between anxiety levels and the occurrence of Premenstrual Syndrome (PMS) with a p-value = 0.00; p < 0.05. The Prevalence Ratio (PR) was 1.6 (95% CI: 1.0–2.6), indicating that respondents with severe anxiety had a 1.6 times higher risk of experiencing PMS compared to those with mild anxiety. The study recommends the need for educational efforts to prevent the further impact of anxiety levels among female adolescents during PMS.